The effect of age and body mass index on dietary health risks assessment of heavy metals from Channa Striatus fish intakes from paddy field - Vivien, How; Khamarudin, Ernney Shuheida; Mohkhtar, Nurul Nadiah (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2021)
Introduction: Trace heavy metal accumulation in pesticide-treated paddy fields was shown to be associated with its concentration in soil and irrigation water, which was affected by soil organic matter and soil/water pH present in the environment. Fish raising and paddy growing are commonly found at pesticides-treated farmland as sources of income and dietary protein intake. Considering the increasing number of metabolic disorders among the elderly from rural communities, the purpose of this study is to determine the concentration of heavy metals (lead and arsenic) in the Channa Striatus by examining the effects of age and body mass index (BMI) on the assessment of human dietary health risks in a rural agricultural community. Methods: Two kilograms of Channa Striatus were collected during the paddy harvest season to examine the heavy metals and 120 farmers were recruited to examine their dietary intakes of Channa Striatus to estimate the potential dietary health risks, that include non-carcinogenic (Hazard Quotient, HQ) and lifetime cancer risk (LCR). Results: Findings show that both lead and arsenic were found not to exceed the permitted level in the Channa Striatus. However, the estimated non-carcinogenic health risks (HQ) and carcinogenic health risks (LCR) of heavy metals dietary intake of Channa Striatus were found to increase proportionally with age and BMI. Conclusion: Although lead and arsenic residues found in fish were lower than the permitted levels, lifetime accumulative of low levels consumption of the contaminated fish that increased with ages and BMI are of concern for its possible chronic health risks.